Optimizing the cascade of prevention to protect people from tuberculosis: A potential game changer for reducing global tuberculosis incidence. - Alberto Matteelli; Gavin Churchyard; Daniela Cirillo; Saskia den Boon; Dennis Falzon; Yohhei Hamada; Rein M G J Houben; Avinash Kanchar; Afrânio Kritski; Blessina Kumar; Cecily Miller; Dick Menzies; et al. (Public Library of Science (PLoS), 2024)
The provision of tuberculosis preventive treatment is one of the critical interventions to reduce tuberculosis incidence and ultimately eliminate the disease, yet we still miss appropriate tools for an impactful intervention and treatment coverage remains low. We used recent data, epidemiological estimates, and research findings to analyze the challenges of each step of the cascade of tuberculosis prevention that currently delay the strategy implementation. We addressed research gaps and implementation bottlenecks that withhold key actions in tuberculosis case finding, testing for tuberculosis infection, provision of preventive treatment with safer, shorter regimens and supporting people to complete their treatment. Empowering communities to generate demand for preventive therapy and other prevention services in a holistic manner and providing adequate financial support to sustain implementation are essential requirements. The adoption of an effective, universal monitoring and evaluation system is a prerequisite to provide general and granular insight, and to steer progress of the tuberculosis infection strategy at global and local level.